Educação para a sustentabilidade e sistema de gestão integrado: um estudo junto ao centro de lançamento da barreira do inferno, Parnamirim - RN - Leal, Aimée Malzac (2016)
This research aims to analyze the links between the Education for Sustainability - EfS and the Integrated Management System - IMS in a military organization. To reach the main objective, four specific objectives have been established: (a) characterize the IMS and its contribution to EfS; (b) verify the expectations of management regarding the use of IMS; (c) verify if, due to the implementation of IMS, reflections and changes in attitudes can be noticed regarding environmental issues both in the professional and personal context of workers; (d) identify the links between IMS and EfS in the institution. After an initial literary analysis in organizational and educational areas, this qualitative research was developed through a case study applied to the Barreira do Inferno Launch Center (CLBI), as it is the first organization of Brazilian Air Force to implement the Integrated Management System practices. The research was conducted with the civil and military servants of CLBI, 4 respondents from the perspective of management, and 21 respondents as collaborators in the period from june to august 2016. The data exploration was guided by the comprehensive-interpretative analysis proposed by Silva (2005). The results reveal 9 links established by the Integrated Management System and the Education for Sustainability. The found links are: (a) legal, the legislation supports the system, in particular in the area of compliance with environmental standards, which include the awareness of workers duties and raising awareness around the subject; (b) instrumental, EfS is a management tool to achieve the environmental goals and occupational health and safety, as the work becomes safer when workers hold a critical perception of these instruments of social protection; (c) cultural, in rigid and hierarchical structures, the impact on management systems implementation process is greater, requiring strengthening in the areas of capacity building and training to achieve the desired cultural changes; (d) scientific, the connection of science and management is still seen as a challenge because there is no government incentives to support both iniciatives simutaneous. However, this study shows that the involvement of the scientific community in the implementation of a management process can generate good results; (e) social interaction, agencies must endeavor to use all human and financial potential for the benefit of the community, pursuing its social function, not focusing only in its internal activities; (f) human development, organizations are responsible for training its members, as they must develop skills that relate to the environment and their implications, in addition to the skills of their duties; (g) financial, monetary contribution received by the federal government does not specifically include the areas of IMS, so managers need to find alternative solutions to make adjustments, especially in the educational process; (h) prevetion, preventive works avoid potential damage of daily activities. Encouraging prevention drives employees mindfulness about the risks involved in their daily activities; (i) personal impact, IMS blended with EfS created a personal and professional awareness on workers, as they were more consciouss that CLBI’s area belongs to the society and it should be preserved by each of them as civil servant and citizens. Another fact that emerged from from this study is that, when there is application of a management tool aimed at sustainability, it is possible to identify personal and professional impact on the lives of employees and other impacts and benefits for the local community.